2017
DOI: 10.1159/000481559
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-196b Inhibits Cell Growth and Metastasis of Lung Cancer Cells by Targeting Runx2

Abstract: Background/Aims: Lung cancer is one of the most common causes of cancer related deaths worldwide. The role of several microRNAs (miRNAs) including miR-196b in different cancers has already been established. The study was aimed to explore the role of miR-196b in lung cancer and its possible underlying mechanism. Methods: Human lung cancer cell line A549 was transfected with miR-196b mimic, miR-196b inhibitor and corresponding controls. Then cell viability, migration, invasion, and apoptosis of A549 lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Previous studies have reported that miRNAs modulate the expression of >50% of human protein-coding genes involved in the regulation of a wide range of physiological and pathological processes, including cell proliferation, cycle, apoptosis, differentiation, metabolism and tumorigenesis (8). Several miRNAs have been demonstrated to be aberrantly expressed in the majority of human malignancies (9)(10)(11). Abnormally expressed miRNAs may result in the progression or inhibition of normal cell growth patterns, thus leading to cancer initiation and progression (12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that miRNAs modulate the expression of >50% of human protein-coding genes involved in the regulation of a wide range of physiological and pathological processes, including cell proliferation, cycle, apoptosis, differentiation, metabolism and tumorigenesis (8). Several miRNAs have been demonstrated to be aberrantly expressed in the majority of human malignancies (9)(10)(11). Abnormally expressed miRNAs may result in the progression or inhibition of normal cell growth patterns, thus leading to cancer initiation and progression (12).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars reported that miRNAs function in different types of human cancer. For example, Bai et al (11) revealed that miRNA-196b suppressed cell metastasis and proliferation by inhibiting Runx2 in lung cancer. Wang et al (12) reported that miR-101 suppressed proliferation and migration of breast cancer cells by targeting SOX2.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, RUNX2 is abnormally expressed in highly metastatic prostate cancer cells and may function as a key regulator in prostate cancer metastatic bone disease [12,13]. Targeting of RUNX2 is found to impair the progression of breast cancer to metastatic bone disease [14] and repress cell growth and metastasis of lung cancer cells [15]. In addition, RUNX2 can promote the metastasis of human gastric cancer through up-regulation of the chemokine receptor CXCR4 [16].…”
Section: Introductionmentioning
confidence: 99%